2020
DOI: 10.1002/jpen.1976
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Handgrip Strength in Hospital Admission Predicts Prolonged Hospital Stay and Death but Is Not Accurate to Identify Malnutrition: A Longitudinal Study of Reduced Handgrip Strength in Hospitalized Patients

Abstract: Background Malnourished patients present impairment of functionality due to loss of strength and muscle mass. However, the validity of handgrip strength (HGS) in identifying malnutrition and its association with clinical outcomes in hospitalized patients requires investigation. Aims Evaluate the accuracy of HGS in identifying malnutrition, its association with clinical outcomes, and the change in HGS in the first 2 weeks of hospitalization. Methods A prospective cohort study with adult/elderly patients. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…Our findings were similar to previous study that HGS could predict prolonged hospital stay in hospitalized patients. 10 Although reduced HGS did not provide satisfactory accuracy to identify malnutrition, HGS is a potential assessment to enhance nutrition assessment. 10,18 However, clinicians or therapists should take note that malnutrition is associated with increased morbidity and clinical complications, higher risk of infections and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to previous study that HGS could predict prolonged hospital stay in hospitalized patients. 10 Although reduced HGS did not provide satisfactory accuracy to identify malnutrition, HGS is a potential assessment to enhance nutrition assessment. 10,18 However, clinicians or therapists should take note that malnutrition is associated with increased morbidity and clinical complications, higher risk of infections and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have shown that pre-operative HGS was associated with patients’ LOS. 10,11 In the meantime, limited studies have investigated the relationship between HGS and long-term validated functional outcomes. 1214…”
Section: Introductionmentioning
confidence: 99%
“…In our population, 47.36% had low muscle strength. This was an independent predictor of poor patient outcomes such as persistent fatigue, diminished capacity to perform activities of daily living, pulmonary function, physical functioning, prolonged hospital stay, poor health-related quality of life, and mortality in other populations [ 11 , 12 , 15 , 16 , 30 32 ]. Cheval et al also showed that muscle strength was an independent risk factor for COVID-19 hospitalization (OR: 0.64, 95% CI: 0.45–0.92, p = 0.015) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort study involving geriatric inpatients ( n = 1406), sarcopenia was associated with 3-month and 1-year mortality in males (HR 3.72; 95% CI 2.06–6.72; HR 1.92; 95% CI 1.34–2.77) and females (HR 2.95; 95% CI 1.56–5.60; HR 2.93; 95% CI 1.89–4.54) [ 35 ]. Studies involving patients with different types of cancer, pooled in a systematic review with meta-analysis, showed an overall HR on cancer mortality of 1.69 (95% CI 1.56–1.83) for patients with sarcopenia [ 36 ]. In a bi-centered prospective cohort study conducted with older individuals, MSS, sarcopenia, sarcopenia with malnutrition risk, and malnutrition groups were independently associated with all-cause mortality at two years.…”
Section: Discussionmentioning
confidence: 99%